Improving the Ability of Implementing Fun-Based Learning Through Structured Clinical Supervision on Mathematics Teachers at SMA Negeri 1 Barru, Indonesia - Gani, Abdul (Journal of Applied Science, Engineering, Technology, and Education, 2021)
This study aimed to determine how much the increase in the ability of implementing fun-based learning for the mathematics teachers of SMA Negeri I Barru through structured clinical supervision. The method used in this study was a school action research. The population of this study were all mathematics teachers at SMA Negeri 1 Barru which consisted of 6 teachers: 3 males and 3 females. This study was conducted in the odd semester of the 2019/2020 school year for 6 meetings. Data in this study were collected by using observation sheets and structured clinical supervision observation instruments ranging from pre-observation, the observation of learning implementation to the observation of feedback implementation for each supervised teacher. The data were analyzed by using qualitative and quantitative descriptive analysis. The overall results of this study were based on the implementation of structured clinical supervision starting from the results of pre-observation of the teaching and learning preparation: syllabus, lesson plans for teaching materials and assessment instruments, as well as the results of observation of the assessment of the learning process.